The Influence of Sales Promotion, Brand Trust, and Ease of Use on Customer Loyalty: A Study on Students of UPN "Veteran" East Java: Pengaruh Promosi Penjualan, Kepercayaan Merek, dan Kemudahan Penggunaan terhadap Loyalitas Pelanggan Studi pada Mahasiswa UPN "Veteran" Jawa Timur - Munthe, Gokma Uli Roma Arta; Nurhadi (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2024)
The purpose of this research is to understand how sales promotion, brand trust, and ease of use affect customer loyalty (Study on students of UPN "Veteran" East Java). An explanatory research method with a quantitative approach was employed, with 157 respondents from UPN "Veteran" East Java. The sampling technique used was purposive sampling with a nonprobability sampling method. Data analysis was conducted using the SPSS software. The findings of this research indicate that simultaneously, sales promotion, brand trust, and ease of use significantly influence customer loyalty. Partially, sales promotion and brand trust have a significant impact on customer loyalty, while ease of use partially does not show a significant influence on customer loyalty